Pemetaan Jalur Evakuasi Banjir di Kecamatan Jatiasih Kota Bekasi - Bahar, Syairul; Fahmi, Fauzi (Sosio-Didaktika: Social Science Education Journal, 2024)
This research aims to determine an effective flood disaster evacuation route in Jatiasih District. The research method used is quantitative descriptive and analyzed using the Geographic Information System (GIS) application. Determining evacuation points takes into account the distribution of settlements, road accessibility and public facilities. Processing evacuation routes using a network analyst based on the closest distance while still considering the condition of the road being traversed. Network analyst processing resulted in 14 evacuation routes connecting 14 initial assembly points (assembly points) with 7 evacuation points (shelter points). From the Network Analyst results and field survey results, it is known that the evacuation route with the longest route is a distance of 1293 meters, namely the route connecting the Al Awwabin Jami Mosque with the Jatiluhur Subdistrict office, while the evacuation route with the shortest route is a distance of 132 meters, namely the route connecting between the Al Fatah Jatiasih Mosque and SDN Jatiasih X. This flood evacuation route can be used as a reference in mitigating floods in Jatiasih sub-district and providing outreach to the community regarding community preparedness in facing floods.